Production of Biodiesel from Seed Oil of Nyamplung (Calophyllum inophyllum) by Al-MCM-41 and Its Performance in Diesel Engine - Hendro Juwono; Triyono Triyono; Sutarno Sutarno; Endang Tri Wahyuni; Ita Ulfin; Fredy Kurniawan (Universitas Gadjah Mada, 2017)
Production of biodiesel from crude nyamplung oil (Calophyllum inophyllum) have been done by transesterification using Al-MCM-41 catalyst. Al-MCM-41 catalyst was obtained from impregnation of MCM-41 by Al. Sodium aluminate was added to MCM-41 until pH 11.5. The mixture was heated until 110 °C for 5 days. The calcination was performed at 500 °C, and then cooled at room temperature. The Al-MCM-41 obtained was characterized using SAXRD. Morphology of the surface was analyzed using SEM. The metals content were measured using XPS. Performance of Al-MCM-41 to adsorp and desorp nitrogen was also monitored by GSA using BET model. Acidity of the Al-MCM-41 was analyzed by FTIR using absorption of pyridine. The catalytic activity was measured using gas chromatography-mass spectrometry (GC-MS). The chromatogram shows that conversion Nyamplung seed oil to biodiesel is 98.15%. The performance of biodiesel obtained was analyzed by use it to diesel engine. The biodiesel obtained was mixed with commercial diesel fuel in various volume ratios (i.e. 0, 10, 20, 30 and 100%) before used. Viscosity, flash point, boiling point, cloud point, and pour point of the mixtures were characterized. These measuring properties increase with the increase of biodiesel concentration. Optimum engine power was achieved by 10% biodiesel. The mixture of 10% biodiesel has similar characteristic to commercial diesel fuel at load until 1800 watt.